New perspectives on construction in developing countries - Ofori, George (New York : Spon, 2012)
"Though the challenges confronting the construction industry in developing countries have grown, current research rarely presents effective solutions. This book focuses on the generic subjects relating to the construction industry in developing countries, and provides an up-to-date insight into important new concepts and issues"--
Includes bibliographical references and index.
Keywords: Construction industry -- Developing countries